INFOGRAPHIC: Insights into the design of practice tasks for learning of decision-making on motor skill of passing in sport of futsal - Correa, Umberto C. (2024)
Access infographic at https://socibracom.com/bjmb/index.php/bjmb/article/view/423/version/457.